Why prevent, diagnose and treat congenital toxoplasmosis? - Rima McLeod; Francois Kieffer; Mari Sautter; Tiffany Hosten; Herve Pelloux (Memorias do Instituto Oswaldo Cruz, 2009)
Evidence that prevention, diagnosis and treatment of toxoplasmosis is beneficial developed as follows: anti-parasitic agents abrogate Toxoplasma gondiitachyzoite growth, preventing destruction of infected, cultured, mammalian cells and cure active infections in experimental animals, including primates. They treat active infections in persons who are immune-compromised, limit destruction of retina by replicating parasites and thereby treat ocular toxoplasmosis and treat active infection in the fetus and infant. Outcomes of untreated congenital toxoplasmosis include adverse ocular and neurologic sequelae described in different countries and decades. Better outcomes are associated with treatment of infected infants throughout their first year of life. Shorter intervals between diagnosis and treatment in utero improve outcomes. A French approach for diagnosis and treatment of congenital toxoplasmosis in the fetus and infant can prevent toxoplasmosis and limit adverse sequelae. In addition, new data demonstrate that this French approach results in favorable outcomes with some early gestation infections. A standardized approach to diagnosis and treatment during gestation has not yet been applied generally in the USA. Nonetheless, a small, similar experience confirms that this French approach is feasible, safe, and results in favorable outcomes in the National Collaborative Chicago-based Congenital Toxoplasmosis Study cohort. Prompt diagnosis, prevention and treatment reduce adverse sequelae of congenital toxoplasmosis.